Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/1365-2664.12739
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of plant materials for ecological restoration: insights from the applied and basic literature

Abstract: Summary Restoration is normally conducted with the goal of creating plant populations that establish, survive, successfully reproduce, contribute to ecosystem function and persist in the long term. Restoration often relies on revegetation that, on large scales, requires agronomic increase of native plant materials. During this propagation process, restoration populations are subject to genetic sampling as well as natural and artificial selection that could result in adaptation contrasting sharply with that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 76 publications
(161 citation statements)
references
References 163 publications
4
145
1
Order By: Relevance
“…Plasticity in traits important for restoration success has been found for self‐fertilizing cultivars of perennial grasses, but not for an outcrossing, genetically diverse, prevariety germplasm (Espeland et al., ). Our study illustrates the importance of plasticity to persistence and evolution of local seed sources in restoration environments and propagule increase fields (Dyer, Knapp, & Rice, ; Espeland et al., ; Nevill et al., ); other research has shown the importance of plasticity to large‐scale restoration seeding with cultivars (Espeland et al., ).…”
Section: Discussionsupporting
confidence: 64%
“…Plasticity in traits important for restoration success has been found for self‐fertilizing cultivars of perennial grasses, but not for an outcrossing, genetically diverse, prevariety germplasm (Espeland et al., ). Our study illustrates the importance of plasticity to persistence and evolution of local seed sources in restoration environments and propagule increase fields (Dyer, Knapp, & Rice, ; Espeland et al., ; Nevill et al., ); other research has shown the importance of plasticity to large‐scale restoration seeding with cultivars (Espeland et al., ).…”
Section: Discussionsupporting
confidence: 64%
“…, Espeland et al. ). The simple approach of selecting warmer adapted genets assumes that predictions of environmental conditions are known and that there are no ecological trade‐offs in phenotypes (e.g., poor reproductive performance or poor disease resistance in heat‐tolerant genets).…”
Section: Choosing Coral Colonies For Restoration: Who and From Where?mentioning
confidence: 99%
“…Data from other systems demonstrate that after removal of initial culture selection, species can adapt to wild conditions rapidly, especially if time spent in captivity is short (Espeland et al. , but see Horreo et al. ).…”
Section: Future Research Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extreme cases of this type of selection are native plant cultivars or other improved varieties. Not only are improved varieties often phenotypically invariant (Espeland & Hammond, ; Leger & Baughman, ) and therefore unlikely to respond to selection imposed by climate change and other adaptive hurdles (Espeland et al., ), but they have often been developed specifically for traits such as above‐ground biomass accumulation, herbicide tolerance, or suitability for mechanized harvesting (Chivers, et al and references therein) that may be maladaptive in the long term in some restoration environments (Leger & Baughman, ). Although cultivars and non‐native species might be considered the most cost‐effective and readily available seed varieties when short‐term goals like soil stabilization cannot be achieved with native accessions (D'Antonio & Meyerson, ; Jones, Monaco, & Rigby, ), they cannot be considered a cost‐effective choice when the goal of restoration is to sustain diverse native landscapes and the native wildlife that depend on them (Kuebbing & Nuñez, ).…”
Section: Introductionmentioning
confidence: 99%